Investigation of the Effects of Marble Material Properties on the Surface Quality - Sümeyra Cevheroğlu Çıra; Ahmet Dağ; Askeri Karakuş (Advances in Materials Science and Engineering)
This study aims to investigate the effects of material properties of marble on surface roughness and glossiness. For this purpose, four types of limestones were investigated. Physicomechanical properties of samples were determined through laboratory measurements. Mineralogical and petrographical characterizations were made using thin-section analysis. X-ray fluorescence (XRF) semiquantitative method was used for chemical analysis. Six different grinding-polishing tests for each marble unit were done under fixed operational conditions using the same abrasive series. Relationship between the material properties and the surface quality was investigated. Although the polishing-grinding tests were conducted under the same operational conditions, different levels of roughness and glossiness were observed on different samples. Data obtained from the study proved that the main cause of this difference is textural and chemical composition variations of the marble specimen. Moreover, statistical evaluations showed that porosity, uniaxial compressive strength, and indirect tensile strength have strong effects on the surface roughness and glossiness of the marble specimen. The presence of an inverse relationship between the glossiness and roughness levels was determined as the result of this study as well.